Morphology and distribution of some new pelagic ostracods of genus Metaconchoecia (Halocyprida: Halocyprididae) from the North Pacific - Chavtur, Vladimir Grygorjevich (Zootaxa, 2003)
Four new species and one subspecies of halocypridids belonging to the genus Metaconchoecia Kock, 1992 have been found inhabiting depths ranging from 25 to 7140 m in the subtropical and temperate regions of the North Pacific (including Sea of Okhotsk and Bering Sea). These new halocyprids are named as M. longiseta nov sp. , M. alta nov. sp., M. ampla nov. sp., M. crassiseta nov. sp. and M. inflata lata.nov. ssp. Their morphology and vertical distribution of two mass species (M. longiseta and M. alta) are described in areas of the Kurile-Kamchatka and Aleutian Trenchs.